Ultrasound assessment of gastric emptying time after intake of clear fluids in children scheduled for general anesthesia—A prospective observational study. Issue 12 (7th November 2020) - Beck, Christiane E.; Chandrakumar, Thurgkai; Sümpelmann, Robert; Nickel, Katja; Keil, Oliver; Heiderich, Sebastian; Boethig, Dietmar; Witt, Lars; Dennhardt, Nils
Abstract: Background: While many clinics have changed their local regimen toward a more liberal policy regarding clear fluid fasting for general anesthesia, there is a lack of studies evaluating gastric emptying time in a clinical setting. Aims: Based on this and before implementation of a more liberal preoperative clear fluid fasting policy for children, we studied gastric emptying time of clear fluids in children and hypothesized that the mean gastric emptying time would be 1 hour. Methods: Between March and December 2019, children scheduled for general anesthesia at our University Children's Hospital were enrolled in this prospective observational study. After overnight fasting, gastric emptying was examined by sonographic measurements of the gastric antral area before and 5, 15, 30, 45, and 60 minutes after intake of water or fruit juice. Results: Twenty‐six children were enrolled in this study, and 24 aged 11 (range 4‐17) years were included for statistical analysis. The median ingested fluid volume was 4.7 (range 1.8‐11.8) mL kg −1 . The gastric antral area of the children initially increased and subsequently decreased after intake of clear fluids and correlated significantly with fasting time ( r = −0.55, P < .0001). After 1 hour, the gastric antral area had returned to the baseline level in 20 children but not in four children with a fluid intake >5 mL kg −1 . There was no difference in the gastric antral area between water and fruit juice. Using a linear regression model, the calculated mean gastric emptying time of clear fluids was 52 minutes. Conclusion: This study showed that the gastric emptying time of children after intake up to 5 mL kg −1 clear fluids was <1 hour in a clinical setting. These results support the more liberal fasting regimen favoring a 1‐hour fasting time and suggest 5 mL kg −1 as an upper limit for clear fluids (eg, water, sugared water or tea or diluted fruit juice) from 2 hours to 1 hour before induction of anesthesia in children.